SOLUSI TERHADAP PERMASALAHAN DALAM IMPLEMENTASI MODEL PEMBELAJARAN SHARINGPLUS UNTUK MENIGKATKAN KUALITAS TUGAS SISWA YANG DIHADAPI OLEH GURU PADA MATA PELAJARAN BAHASA INGGRIS DI SMP MUHAMMADIYAH 6 PADANG - Siska Siska; Yelfiza Yelfiza (FKIP Universitas Citra Bangsa, 2022)
The teaching and learning method used at SMP Muhammadiyah 6 Padang is the assignment method. But , the students still get difficulties to do assignments because they do not understand. Therefore, SHARINGPLUS is very important to be socialized by the English Education Service Team at PGRI West Sumatra University to provide solutions faced by students at SMP Muhammadiyah 6 Padang. Where, teachers will be given an understanding or knowledge of the theoretical concepts of SHARINGPLUS and practical concepts so it can change students' negative behavior in doing assignments into positive behavior.